Instagram-Based Promotional Strategy and Digital Brand Visibility at Gunsas Resto - Silfia Silfia; Khitara Aldilla Chandra (Lentera Ilmu Nusantara, 2026)
The increasing competition in the culinary industry requires restaurants to manage digital promotion through measurable and audience-oriented strategies. This study aims to examine Instagram promotional content effectiveness as an indicator of digital brand visibility and early-stage digital brand awareness at Gunsas Resto. A descriptive quantitative approach with a case study design was applied. The study used secondary data from Instagram performance reports of Gunsas Resto and Gunsas Duren, covering posts published from January 2025 to May 2026. After data cleaning, 117 valid Instagram posts were analyzed using social media analytics indicators, including views, likes, saves or reposts, shares, direct messages, comments, profile visits, follower growth, and engagement rate. This study does not directly measure consumer brand recall or brand recognition; instead, it uses Instagram analytics indicators as proxies for digital exposure, audience response, and early signals of brand awareness. The findings show that the analyzed content generated 126,908 views and 7,339 interactions, with a weighted engagement rate of 5.78%. Gunsas Duren achieved stronger performance than Gunsas Resto, indicating that product-focused content generated higher digital exposure and audience response. Reels produced the highest average views, while photo-based content generated the highest weighted engagement rate. These results indicate that short-form video is effective for expanding reach, whereas product-oriented visual content is more effective in strengthening engagement. Practically, this study helps Gunsas Resto develop a more measurable Instagram strategy by aligning content formats with promotional objectives and using analytics to evaluate content performance regularly.